Overview of programmed electrical stimulation to assess atrial fibrillation susceptibility in mice - Murphy, Matthew B.; Kannankeril, Prince J.; Murray, Katherine T. (Frontiers in Physiology, 2023)
Atrial fibrillation (AF) is the most common human arrhythmia and is associated with increased risk of stroke, dementia, heart failure, and death. Among several animal models that have been used to investigate the molecular determinants of AF, mouse models have become the most prevalent due to low cost, ease of genetic manipulation, and similarity to human disease. Programmed electrical stimulation (PES) using intracardiac or transesophageal atrial pacing is used to induce AF as most mouse models do not develop spontaneous AF. However, there is a lack of standardized methodology resulting in numerous PES protocols in the literature that differ with respect to multiple parameters, including pacing protocol and duration, stimulus amplitude, pulse width, and even the definition of AF. Given this complexity, the selection of the appropriate atrial pacing protocol for a specific model has been arbitrary. Herein we review the development of intracardiac and transesophageal PES, including commonly used protocols, selected experimental models, and advantages and disadvantages of both techniques. We also emphasize detection of artifactual AF induction due to unintended parasympathetic stimulation, which should be excluded from results. We recommend that the optimal pacing protocol to elicit an AF phenotype should be individualized to the specific model of genetic or acquired risk factors, with an analysis using several definitions of AF as an endpoint.